Program Psikoedukasi untuk Meningkatkan Literasi Kesehatan Mental Santri Buntet Pesantren Cirebon - Sapari Sapari; Yusuf MZ; Muhamad Mujadid; Adib Rofiuddin Basori (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
Adolescent mental health, particularly among santri is a critical issue requiring serious attention. This community engagement initiative aimed to enhance mental health literacy at Pondok Buntet Pesantren using a Participatory Action Research (PAR) approach, comprising three main phases: initial assessment, psychoeducation, and counseling guidance. Thirty-six participants completed pre- and post-test evaluations using standardized instruments, specifically the Satisfaction with Life Scale and the Mental Health Literacy Scale. The results indicated a significant increase in students' life satisfaction following the intervention. Although improvements in positive emotions and mental health literacy were not statistically significant, the observed positive trends suggest the program's effectiveness in deepening understanding, reducing stigma, and serving as a crucial preventive measure for maintaining students' mental well-being.